Penteo spettatore di tragedia: le Baccanti e la risposta alle Tesmoforiazuse (Argos, 2025)
Based upon a detailed analysis of the structural and thematic analogies that link together Bacchae and Thesmophoriazusae, the article assumes that this tragedy might contains a reply to the parody of the tragic poet in the middle of Thesmophoriazusae.
Keywords: Bacchae; Thesmophoriazusae; poetic rivalry